2022
DOI: 10.3390/nano12173043
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nanosized CoTiO3 Synthesized via a Solid-State Method on the Hydrogen Storage Behavior of MgH2

Abstract: Magnesium hydride (MgH2) has received outstanding attention as a safe and efficient material to store hydrogen because of its 7.6 wt.% hydrogen content and excellent reversibility. Nevertheless, the application of MgH2 is obstructed by its unfavorable thermodynamic stability and sluggish sorption kinetic. To overcome these drawbacks, ball milling MgH2 is vital in reducing the particle size that contribute to the reduction of the decomposition temperature. However, the milling process would become inefficient i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 76 publications
1
3
0
Order By: Relevance
“…This revealed that the addition of Ni 0.6 Zn 0.4 O as an additive to MgH 2 resulted in a notable decrease in the kinetic barrier desorption of the MgH 2 system, which is beneficial for hydrogen release from MgH 2 . These findings are also consistent with earlier research that showed the addition of an additive or catalyst lowers the activation energy of MgH 2 [ 56 , 57 ]. Zhang and co-workers [ 58 ] exposed that the reaction energy barrier for the desorption reduced to 109 kJ/mol when MnMoO 4 was doped to MgH 2 .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This revealed that the addition of Ni 0.6 Zn 0.4 O as an additive to MgH 2 resulted in a notable decrease in the kinetic barrier desorption of the MgH 2 system, which is beneficial for hydrogen release from MgH 2 . These findings are also consistent with earlier research that showed the addition of an additive or catalyst lowers the activation energy of MgH 2 [ 56 , 57 ]. Zhang and co-workers [ 58 ] exposed that the reaction energy barrier for the desorption reduced to 109 kJ/mol when MnMoO 4 was doped to MgH 2 .…”
Section: Resultssupporting
confidence: 93%
“…As expected, MgH 2 –10 wt.% Ni 0.6 Zn 0.4 O samples exhibited a smaller particle size as compared with milled MgH 2 (as can be seen in Figure 7 c). Ali et al [ 56 ] introduced CoTiO 3 to MgH 2 and showed that the particle size of the composite changed to a finer and smaller size. According to the research results of Somo et al [ 63 ], smaller particle sizes allow quick dissociation into the surface of materials.…”
Section: Resultsmentioning
confidence: 99%
“…Without any prior processing, LiAlH 4 (95% pure) from Sigma Aldrich was used. The nanosized CoTiO 3 was synthesised via the solid-state method, as explained in our previous work [ 33 ]. Then, various amounts of CoTiO 3 (5 wt.%, 10 wt.%, 15 wt.% and 20 wt.%) were doped with LiAlH 4 to study its influence on the desorption behaviour of LiAlH 4 .…”
Section: Methodsmentioning
confidence: 99%
“…Carbon also provided a confinement effect which also aided the stability of MgH2 during de/hydrogenation cycles. Ali et al (2022) doped MgH2 with 10 wt.% CoTiO3. Hydrogen was desorbed at 270 o C, which was lower than that of MgH2 that occurred at 340 o C. Within the first 10 min, 6.4 wt.% H2 was adsorbed.…”
Section: Cobalt (Co)mentioning
confidence: 99%